Efeitos do estresse agudo e crônico sobre o sistema serotonérgico de diferentes subnúcleos do núcleo dorsal da rafe - Lopes, Danielle Abreu [UNIFESP] (2015)
The concept of stress is based on the observation that different types of stimuli (external or internal) that threaten homeostasis induce a set of bodily changes, called "general adaptation syndrome". The term stimulus or stressor corresponds to events or circumstances that are perceived as aversive by the individual, generating the so-called stress response or stress condition, involving visceral, neuroendocrine and behavioral responses. This set of responses aim at maintaining the body homeostasis / allostasis, and by themselves are not pathological. However, when the aversive stimulation occurs for a prolonged period or exceeds the body's ability to maintain homeostasis / allostasis, stress can cause pathological sequelae. One of the major neurotransmitter systems that appear to be dysregulated in stress-related disorders such as anxiety and depression is the serotonergic system, originating from the dorsal raphe nucleus (DRN). In previous studies, we verified that exposure to acute restraint and to unpredictable chronic mild stress (UCMS) increased anxiety-related behavior and Fos-immunoreactivity in different brain areas, including the dorsal raphe (DR). Since, it has been shown that the DR is composed by distinct subpopulations of serotonergic and non-serotonergic neurons, the present study investigated the pattern of activation of these different subnuclei of the region in response to acute and chronic stressors. Male Wistar rats were either unstressed or exposed to acute restraint or to the UCMS procedure for two weeks and, subsequently, analyzed for Fos protein-immunoreactivity (Fos-ir), tryptophan hidroxilase enzyme immunoreactivity (TrpOH-ir) and double-labeling (Fos/TrpOH-ir) in serotonergic cells of the DR. For comparison reasons, the median raphe (MR) nucleus was also evaluated. Results showed that the UCMS procedure increased Fos-ir and the number of double-labeled neurons in the mid-rostral subdivision of the dorsal part of the DR and in the mid-caudal region of the lateral wings. In this last region, there was also a significant increase in the number of tryptophan hydroxylase immunoreactive cells. Although both acute restraint and UCMS exposure increased Fos-ir in the MR, only acute restraint increased double immunolabeling in this region. This data indicates that acute restraint and UCMS exposure differently activate the DR and the MR, corroborating the idea that these regions play distinct roles in the regulation of stressrelated responses.